Savonius Turbine Performance Type ”“ S Variation of Rotor Sweep Diameter and Air Gap - Margana, Margana; Sumarno, F Gatot; Purwati W, Wiwik; Suwarti, Suwarti; Fakhri Dzulfikar, Hafidh; Ibrahim, Nandhi Lathief; Wahyuningtyas, Saskia; Widya Larassanti, Sri; Naufal Hanif, Daffa”™ (Politeknik Negeri Semarang, 2022)
The savonius wind turbine with variations in the diameter of the sweep and the air gap is a technological innovation with treatment using changes in the diameter of the sweep and the distance of the air gap between the blades. And it has low self-starting and relatively high torque. The purpose of the study was to create five models and test the performance of the Savonius wind turbine with variations in sweep diameters of 500 mm, 480 mm, 460 mm, 440 mm and 420 mm with air gaps of 30 mm, 50 mm, 70 mm, 90 mm, and 110 mm. . And analyze the turbine performance to get the best Coefficient of Power (CP) from the five turbine gaps. The stages of the research method include the preparation of a literature search, turbine design planning, tool making, tool testing, data collection, data analysis, and the final stage. The results of the tests carried out showed that the Savonius turbine with an air gap of 70 mm with a CP value of 0.232 had maximum work at low wind speeds (4 m/s) and at high wind speeds (10 m/s). obtained a CP value of 0.0695